PENGARUH KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KEPEMUDAAN, OLAHRAGA DAN PARIWISATA KOTA PAREPARE - Hartati Hartati; Megawati Beddu (Jurnal Ilmu Manajemen Profitability, 2020)
The purpose of the study was to determine the effect of job satisfaction and work environment on employee performance at the Youth, Sports, and Tourism Office of Parepare City. Data collection techniques in this study were interviews, questionnaires, and observation. The population in this study amounted to 32 employees at the Office of Youth, Sports, and Tourism of Parepare City. The sampling technique in this research is saturated sampling. The sample in this study were 28 permanent employees and 4 non-permanent employees) at the Youth, Sports, and Tourism Office of Parepare City. The results showed that job satisfaction had a positive and insignificant effect on performance with a regression coefficient value of 0.340 and a probability value of 0.037 0.005. Partially job satisfaction also affects performance in terms of the t-count value of 2.189 t-table 2.045. The work environment has a positive and significant effect on performance with a regression coefficient value of 0.554 and a probability value of 0.003 0.005. Partially, the work environment also affects performance in terms of the t-count value of 3.226 t-table 2.045. Job Satisfaction and Work Environment simultaneously affect performance as seen from the calculated F value of 10,797 F table 3,32.